The Role of Additional Ceramic Waste on Expansive Clay Stability - Agus Tugas Sudjianto; Aji Suraji (Widyagama University of Malang, 2022)
One of the construction problems is often due to poor technical properties of the soil, unstable soil, and poor soil bearing capacity is one of the causes of high shrinkage expansion. The purpose of this study was the use of ceramic waste as a stabilizing agent for expansive clay. Expansive clay samples were taken in undisturbed and disturbed conditions. Variations in addition of ceramic waste to clay are 0%, 5%, 10%, 15% and 20%. Physical properties were tested (moisture content, specific gravity, atterbeg and proctor limits) mechanical properties (free swelling). The results showed that the ceramic handicraft industry waste as a soil stabilizing agent showed that the results of the physical properties decreased in water content and specific gravity was quite consistent. In addition, the stress value increases after mixing ceramic waste are related to mechanical properties, and the longer the incubation day, the higher the swelling volume and the highest swelling volume in a mixture of 5% ceramic waste.